Formation of Professional Enhancement of Specialists on the Basis of Pedagogical Technologies - Lyailya, Koishigulova; Klara, Kabylgazina; Almazhai, Eginissova; Tlegenovna, Utaliyeva Zhanna; Saltanat, Omarova (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
In recent years, in line with the competence-based approach in the domestic and foreign science actively is being developed the problem of formation of professional enhancement "as a mandatory competency component of professional training of modern specialist" in different branches of science - philosophy, sociology, psychology, pedagogy, cultural studies, economics, ethics. Such a multifaceted study of the phenomenon of "training" is determined by the dynamics of the social life of society, the real needs in the research for modern philosophical orientations is the necessity of its formation in the learning process [1].